Development of Health Services in Al-Najaf ‘‘Al Ashraf’’ Governorate-Iraq - Abbas Shabaa, ohammed Jawad; Abas , Ahmed Yhya Abd (International Journal of Psychosocial Rehabilitation, 2020)
Health services have great importance in relation to the health of the population. It is one of the criteria for measuring the state's progress in care; it is also one of the most important factors contributing to sustainable development and one of its indicators both in developed and developing societies.AL-Najaf governorate is one of the most important governorates in Iraq in terms of religious and historical issues, where there is a holy shrine of Imam Ali. This study tries to Diagnosis of weaknesses in the health services in AL-Najaf governorate, and their compatibility with planning standards, and follow the best possible ways and mechanisms for their development. The results of this study indicate that the number of hospitals is very low, where it is noted that some administrative units are empty of hospitals, which are represented in the areas of AL-Mshkab and the Al-Shabka, the indicator(person/ hospital) has reached in AL-Najaf Governorate(110549 person / hospital) in 2018, the indicator (person / health center)reached (20635) in Al-Najaf Governorate and recorded the highest value in the district of Al-Haedreea (58112 people/health center, indicator (person/ doctor) notes that this indicator is good in the governorate and reached a limit close to what was determined by the Ministry of Health, where it reached in the governorate (1012 people/doctor).Weak efficiency of the health system and aging of the infrastructure of health institutions, limited use of administrative governance and the ingredients to update standards of health quality.